Arguing Global Environmental Constitutionalism - Louis J. Kotzé (Revista Opinião Jurídica, 2015)
The current global environmental law and governance regime has been designed primarily to attend to the worsening ecological crisis. Evidence, however, suggests that the regime is far from achieving its goal and it is failing in its efforts to solve what people perceive to be pervasive global environmental problems. There is little doubt that this regime is in need of urgent reforms and/or re-situation in a decidedly different paradigm. This article proposes that global constitutionalism, while no panacea, could contribute to these paradigm-shifting reforms by providing a new perspective through which to view the current deficient global environmental law and governance regime and, in real terms, ameliorating some of the deficiencies of the regime through a normative process of constitutionalization.